Fabrication of Synthetic Lumbar Vertebrae by a Combination of FDM 3D-Printing and PU Foam Casting from Two Injection Techniques for Surgical Training - Farid Triawan; Nisa Khoiriyah; A. Asriyanti; Muhammad Satrio Utomo; Kushendarsyah Saptaji; Nikolas Krisma Hadi Fernandez; Muhammad Akhsin Muflikhun (Bumi Publikasi Nusantara, 2026)
This study aims to introduce a rapid and precise fabrication technique of lumbar vertebrae model that mimics the cortical and cancellous parts of the bone using polylactic acid (PLA) and polyurethane (PU) foam, respectively. An FDM 3D-printing using PLA filament was utilized to fabricate the cortical part, then PU foam was molded into the printed cortical to form the cancellous part. The fabricated model was examined by comparing its dimensions with the stereolithography (STL) model. Sequentially, density measurement, compressive test, and microstructure observation were performed to evaluate the specimen characteristics. The results showed that the dimensions of the vertebrae model agreed well with the STL model, with a discrepancy of less than 4%. The fabricated PU samples exhibited a density in the range of 476–557 kg/m³, elastic moduli of 3.99–7.17 MPa, and a pore size of 136.66–179.80 µm, which are lower than the properties of human bone. Despite that, the PU samples maintain their compressive strength of 0.329–0.589 MPa, which is within the range of cancellous human bone.